2015
DOI: 10.1038/mt.2015.179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Liver Gene Transfer With AAV Vectors Based on Natural and Engineered AAV Capsids

Abstract: Vectors based on the clade E family member adeno-associated virus (AAV) serotype 8 have shown promise in patients with hemophilia B and have emerged as best in class for human liver gene therapies. We conducted a thorough evaluation of liver-directed gene therapy using vectors based on several natural and engineered capsids including the clade E AAVrh10 and the largely uncharacterized and phylogenically distinct AAV3B. Included in this study was a putatively superior hepatotropic capsid, AAVLK03, which is very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 44 publications
9
95
2
Order By: Relevance
“…Additionally, while rAAV8 mediates highly efficient liver transduction in mice, human liver is less efficiently transduced, leading others to favor other serotypes such as AAV5 and the use of hyperactive protein variants such as the Padua mutation of FIX [60,61]. Not satisfied with naturally occurring serotypes, others have used humanized mice (where mouse liver cells are partially replaced with human liver cells) to allow directed evolution of AAV capsid (Figure 2(a)), developing novel serotypes that are better at targeting human cells [62,63]. Similar to the directed evolution approach in human airway epithelial cultures described above, when these novel serotypes increase their tropism for human liver cells, they concomitantly lose tropism for mouse cells.…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…Additionally, while rAAV8 mediates highly efficient liver transduction in mice, human liver is less efficiently transduced, leading others to favor other serotypes such as AAV5 and the use of hyperactive protein variants such as the Padua mutation of FIX [60,61]. Not satisfied with naturally occurring serotypes, others have used humanized mice (where mouse liver cells are partially replaced with human liver cells) to allow directed evolution of AAV capsid (Figure 2(a)), developing novel serotypes that are better at targeting human cells [62,63]. Similar to the directed evolution approach in human airway epithelial cultures described above, when these novel serotypes increase their tropism for human liver cells, they concomitantly lose tropism for mouse cells.…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…These studies have revealed some unique organism, organ, tissue, or cell-type specific transduction pattern after intravascular delivery. For example, AAV-3B showed superior hepatotropism in primate but not rodent liver [114-116]. AAV-4 showed selective cardiopulmonary tropism [117].…”
Section: Re-engineering Aav For Improved Systemic Deliverymentioning
confidence: 99%
“…The nature and abundance of these extracellular glycans vary dramatically between different species and at different developmental stages. Since AAV attachment is a determining factor in systemic delivery, cautions should be taken to extrapolate re-engineered capsids for different applications [102,115,116,137]. …”
Section: Re-engineering Aav For Improved Systemic Deliverymentioning
confidence: 99%
“…They show transduction of nearly 100% of hepatocytes, and expression was maintained for 30 weeks. This result is rather surprising, considering that no one else in the field has been able to achieve uniform liver gene transfer even if all monkeys were prescreened for NABs, because AAV8 strongly prefers hepatocytes near the portal vein structures in NHPs 12,13 . In addition, no one has been able to achieve long-term expression of GFP after AAV administration to the liver of NHPs 14 .…”
Section: To the Editormentioning
confidence: 99%